Tabebuia rosea seed extract mediated synthesis of silver nanoparticles with antibacterial, antioxidant, and antiproliferative activities - Moorthy Muruganandham; Fatimah Oleyan Al-Otibi; Raedah Ibrahim Alharbi; Kanagasabapathy Sivasubramanian; Anon Chaulagain; Palanivel Velmurugan; Nagaraj Basavegowda (Materials Research Express, 2023)
The green synthesis of silver nanoparticles (AgNPs) using plants has grown in significance recently. The present investigation involved the synthesis of AgNPs utilizing Tabebuia rosea (TR) seeds as a reducing agent. The bioactive potential of the synthesized AgNP was evaluated through antibacterial, antioxidant, and cytotoxicity assays. The confirmation of the formation of AgNPs was achieved through the utilization of UV–vis spectroscopy. The spectroscopic analysis revealed the presence of absorption maxima at 450 nm, which is a distinctive feature of AgNPs. The optimization process for the synthesis of nanoparticles was conducted by varying the pH levels, metal ion (AgNO _3 ), and substrate (Seed extract). The size range of the synthesized nanoparticles was found to be less than 100 nm through the use of scanning electron microscopy (SEM). The profile obtained through energy dispersive x-ray spectroscopy (EDX) analysis of AgNPs exhibited a characteristic optical absorption peak at approximately 3 keV. Further investigation using Fourier transform infrared (FTIR) spectroscopy revealed the involvement of O–H stretching in phenolic compounds and O–H and C=O stretching in carboxylic acids forming AgNPs. The results of the antimicrobial activity assay indicate that the bacteria K. pneumonia exhibited the maximum inhibition zone of 20 ± 0.48 mm, followed by E. faecalis , P. aeruginosa , P. mirabilis , and S. aureus at the highest concentration of 100 mg ml ^−1 , respectively. The DPPH assay findings suggest that the maximum concentration of 500 μ g ml ^−1 of AgNPs exhibited a unique scavenging ability, with a value of 80.98%. Additionally, the application of biologically synthesized AgNPs to treated cells resulted in a cytotoxic effect. The inhibitory concentration (IC _50 ) value of 45   μ g ml ^−1 was determined following a 24 h treatment with human fibroblast cells (L929). Using T. rosea seed to produce AgNPs holds promise for their potential application as nano drugs.